Does accreditation of general practice promote patient-reported quality of care? A natural cluster randomised experiment. Issue 6 (11th June 2020) - Riisgaard, Helle; Waldorff, Frans Boch; Kirstine Andersen, Merethe; Pedersen, Line Bjørnskov
Abstract : Objective: To investigate whether accreditation of general practice in Denmark promotes patient-reported quality of care and patient satisfaction. Design: A national cluster randomised case control study based on an online version of the Danish Patients Evaluate Practice questionnaire. Mixed effects ordered logit regression models taking account of clustering of patients in different municipalities were used in the analyses. Setting: General practice in Denmark. Participants: A representative sample of the Danish population. Primary and secondary outcome measures: The primary outcome measure was patient-reported quality of care, and patient satisfaction with general practice and patient satisfaction with the general practitioner served as secondary outcome measures. Results: In total, 3609 respondents answered the survey. We found no statistically significant relationships between patient-reported quality of care and practice accreditation (2016: OR=0.89, 95% CI 0.73 to 1.07 and 2017: OR=0.85, 95% CI 0.71 to 1.02) and between patient satisfaction with the general practitioner and accreditation (2016: OR=0.93, 95% CI 0.76 to 1.13 and 2017: OR=0.86, 95% CI 0.70 to 1.04). However, there was a statistically significant negative relationship between patient satisfaction with the general practice and recent practice accreditation compared with satisfaction with practices not yet accredited (OR=0.81, 95% CI 0.67 to 0.97) but no significant relationship between patient satisfaction with the general practice and previous accreditation (OR=0.91, 95% CI 0.76 to 1.09). Conclusion: Accreditation does not promote patient-reported quality of care or patient satisfaction. On the contrary, patient satisfaction with the general practice decreases when general practice is recently accredited.